Micropropagation of Michelia Champaca L. - Ansari, Arminyati (2009)
The expansion in Champaca industry has led to an increasing demand for planting materials. A study was conducted with the objective of developing plant regeneration system for Michelia champaca L. through organogenesis and somatic embryogenesis. The study was conducted in consideration of the potential economic importance of the species. It consisted of development of sterilization procedure for field grown M. champaca shoot tip and nodal segment explants and plant regeneration through organogenesis and somatic embryogenesis of M. champaca either through solid culture medium and cell suspension culture technique. This was the first report on the establishment of M. champaca cell suspension culture. All experiments in this study were conducted in a Completely Randomized Design (CRD). In the development of sterilization procedure for field grown shoot tips and nodal segments of M. champaca sterilization with 20% of clorox (20 minutes) + 70% alcohol (2 minutes) + 10% clorox (5 minutes) and 0.1% HgCl2 (5 minutes) successfully produced non-contaminated explants up to 80% for field-grown shoot tip and 50% for nodal explants. In the experiment of determination of M. champaca seed viability, different tetrazolium concentrations (0.1, 0.5, and 1 % (w/v)) in combination with different immersion times (1, 2, 4, 6 and 8 hours) were used as treatments. The highest percentage of seed viability (100%) was obtained from all tetrazolium concentrations tested in combination with eight hours of immersion time. Results on plant regeneration via organogenesis showed that MS (Murashige and Skoog, 1962) medium supplemented with 0.2 gL-1 of charcoal, 30 gL-1 (w/v) of sucrose and solidified with 3.9 gL-1 gelrite agar containing BAP at 6 mgL-1 in combination with 0.5 mgL-1NAA was the most suitable for shoot induction from shoot tip derived from seedling explants with the highest mean number of shoots produced per explant (1.8) and mean shoot height of 4.53 cm. Meanwhile treatment containing 0.5 mgL-1 NAA was the most suitable for rooting with a percentage of shoot producing root at 70%, with mean number of roots formed per shoot at 2.5 and mean root length was 1.07 cm.